Cambridge scientific minds - Harman, P. M. 1943-; Mitton, Simon 1946- (Cambridge University Press, 2002)
Since the 'scientific revolution' of the seventeenth century, a great number of distinguished scientists and mathematicians have been associated with the University of Cambridge. Cambridge Scientific Minds provides a portrait of some of the most eminent scientists associated with the University over the past 400 years, including accounts of the work of three of the greatest figures in the entire history of science, Isaac Newton, Charles Darwin and James Clerk Maxwell. The chronological balance reflects the increasing importance of science in the recent history of the University. The book comprises personal memoirs and historical essays, including contributions by leading Cambridge scientists. Cambridge Scientific Minds will be of interest not only to graduates of the University, science students and historians of science, but to anyone wishing to gain an insight into some of the greatest scientific minds in history.
Keywords: University of Cambridge -- History.